Exploring 19th-century medical mission in China: Forging modern roots of Chinese medicine - Zhang, Youheng (Hervormde teologiese studies, 2023)
During the 19th century, missionaries profoundly impacted China's social and scientific advancement. Their efforts faced challenges because of deeply ingrained superstitions and polytheistic traditions. Missionaries adopted diverse approaches such as spreading scientific knowledge, establishing educational institutions and conducting medical missions to further their mission. Notably, medical missions played a vital role in alleviating suffering, eradicating prejudice and fostering opportunities for the spread of Christianity in China. Through providing medical services, missionaries gained trust and goodwill within local communities, showcasing Christian compassion and benevolence. Additionally, they founded medical schools, translated foreign medical works and established medical journals, contributing to the development of modern Chinese medicine to some extent. Contribution This article delves into the medical practices of 19th-century medical missionaries. It asserts that these medical missionaries played a pivotal role in establishing the groundwork for the advancement of modern medicine in China. Furthermore, the article suggests that contemporary missionary activities in China can draw inspiration from the model set by these historical medical missionaries, emphasising the enduring relevance of their approach in conducting effective missionary work today.